Analysis of Family Behavior Factors in Latrine Utilization in Mundek Village, Northwest Rote District, Rote Ndao Regency - Willem Lukas Selan; Petrus Romeo; Marselinus Laga Nur (Lontar : Journal of Community Health, 2021)
The use of latrines for rural communities is a health behaviour problem that needs constant attention due to the inefficient use of healthy latrines. Both internal and external factors influence the use of the latrine. The study purposed to analyze family behaviour factors using latrines in Mundek Village, Northwest Rote District, Rote Ndao Regency. This research was an analytical survey with a cross-sectional design. The sample was 72 people determined based on a simple random technique. The data analysis consisted of univariable analysis and bivariable analysis using the Chi-Square test. The results showed that there was a relationship between the level of knowledge (0.021), attitude (0.000), water availability (0.001) and the use of latrines. On the other hand, there was no relationship between gender (0.796), an education level (0.259) and latrines in Mundek Village, Northwest Rote district, Rote Ndao Regency. Therefore, stakeholders should undertake intensive health promotion to increase the local community's knowledge and change negative attitudes towards healthy latrines utilization.